2020
DOI: 10.2196/17430
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a WhatsApp-Delivered Education Intervention to Enhance Breast Cancer Knowledge in Women: Mixed-Methods Study

Abstract: Background Breast cancer is the leading cause of cancer-related death in the female population. Health education interventions based on the use of mobile technologies enable the development of health self-care skills and have emerged as alternative strategies for the control of breast cancer. In previous studies, WhatsApp has stood out as a useful tool in health education strategies; however, it has not yet been applied for breast cancer education. Objective … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 68 publications
(64 reference statements)
3
36
0
9
Order By: Relevance
“…A recent WhatsApp-based study implemented among Brazilian women to increase breast cancer awareness also pointed out that the interaction between participants was a challenge. 25 The authors noted that women adopted a passive posture for receiving health information, always waiting for the moderator (“expert voice”) to have the final say. 25 …”
Section: Discussionmentioning
confidence: 99%
“…A recent WhatsApp-based study implemented among Brazilian women to increase breast cancer awareness also pointed out that the interaction between participants was a challenge. 25 The authors noted that women adopted a passive posture for receiving health information, always waiting for the moderator (“expert voice”) to have the final say. 25 …”
Section: Discussionmentioning
confidence: 99%
“…After analysing the data, it can be said that the level of awareness in individuals who participated in the studies contained in the research shown increased significantly [43] as a result of the various educational interventions on BC, particularly in aspects concerning new information and early detection methods. This indicates that the educational interventions are effective, managing to significantly increase the level of awareness in all their variants, leading to future quality of life through timely detection, linked with prevention and control of the disease and with improvements in life styles [33,37,[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that in interventions in the 30–65 years age range, there is insufficient knowledge about BC. However, after the educational intervention, there was generally a very good level and following the intervention no women were found to have a poor level of knowledge [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Educational interventions through mobile technologies help promote health due to its simplicity, accessibility, and minimization of the distance, cost, and time barriers (Bradway et al 2017;Oreskovic, Huang, and Moon 2015). A study conducted by (Pereira et al 2020)) showed the benefits of the educative intervention on breast cancer. According to the authors, it is the first study to use WhatsApp as a health education tool destined for Brazilian women on Brazil's public health system that focused on risk reduction and early detection of this disorders.…”
Section: Intervention Studies On Women With Breast Cancermentioning
confidence: 99%